Antibacterial hemostatic hydrogel loaded with composite nanoparticles
By loading ground cytamisone on the Jiekou dopamine nano -ball, combined with blank hydrogel, to prepare antibacterial hemostatic hydrogels with load composite nanoparticles, solving the existing hydrogel in traumatic brain damage to repair neutrality and Chinese mechanical performance and The problem of insufficient stability achieves the effects of hemostatic, anti -inflammatory and neurological factor repair.
Patent Information
- Application Number
- CN202411480069.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2025-01-24
AI Technical Summary
Existing hydrogels lack mechanical properties and stability in the repair of traumatic brain injury, making it difficult to achieve hemostasis, anti-inflammatory and neurofactor repair effects.
By loading the hydrophobic drug dexamethasone on mesoporous polydopamine nanospheres, composite nanoparticles were synthesized and combined with blank hydrogel to form an antibacterial hemostatic hydrogel loaded with composite nanoparticles.
The hydrogel has good antioxidant, anti -inflammatory and inner layers of repair performance, can achieve the controllable release of dexamethasone, has high biocompatibility and tissue affinity. It is suitable for brain injury. Fill and anti -inflammatory repair treatment.
Smart Images

Figure CN119345451A_ABST
Abstract
Description
This patent application is a divisional application of Chinese Patent 202310625649.1, whose invention name is "Preparation method and application of antibacterial hemostatic hydrogel loaded with composite nanoparticles", and its entire text is incorporated herein by reference. Technical Field
[0001] The present invention belongs to the field of biomedical materials and has a classification number of C08J3 / 075. Specifically, the present invention relates to an antibacterial hemostatic hydrogel loaded with composite nanoparticles and a preparation method thereof. Background Art
[0002] Traumatic brain injury (TBI) is one of the common diseases in neurosurgery and one of the major health and socioeconomic problems in the world. The secondary injury mechanism during TBI is an important cause of death, and the secondary injury mainly affects the neuron body, dendrites, synapses and other types of nerve cells.
[0003] Hydrogel is a type of extremely hydrophilic three-dimensional network structure gel that swells rapidly in water and can retain a large volume of water in this swollen state without dissolving. Currently, hydrogel is often used as a wound repair material, but the mechanical properties and stability of hydrogel are generally poor, which can easily lead to wound exposure and increase the risk of infection. Moreover, it only has antibacterial properties and cannot achieve the effects of anti-inflammatory and repairing neural factors. Therefore, the development of hydrogel in the field of repairing traumatic brain injury needs to be promoted.
[0004] Chinese patent CN114984244A discloses a hyperbranched polylysine-containing hydrogel carrier material and a preparation method thereof, wherein the hyperbranched polylysine and aldehyde hyaluronic acid are simply physically mixed to form a hydrogel, and then the drug and the hydrogel are simply mixed by ultrasound. Although the hydrogel has an anti-inflammatory effect to a certain extent, it cannot achieve the effect of hemostasis and repairing nerve factors, and the drug release rate is low and the stability is not high when the drug and the hydrogel are simply mixed.
[0005] Chinese patent CN114668897B discloses an antibacterial, adherent, injectable, and healable hydrogel, and its preparation method and application. The hydrogel synthesized by quaternized chitosan, mesoporous polydopamine nanoparticles, gelatin and other ingredients has certain mechanical properties, adhesion, self-healing properties, and antibacterial properties, but it cannot achieve hemostatic and anti-inflammatory effects. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present invention provides a method for preparing an antibacterial hemostatic hydrogel loaded with composite nanoparticles, characterized in that it comprises the following steps: (1) synthesis of composite nanoparticles; the composite nanoparticles are composed of mesoporous polydopamine nanospheres loaded with hydrophobic drugs; (2) synthesis of blank hydrogel; the blank hydrogel is formed by mixing liquid A and liquid B; (3) synthesis of drug-loaded hydrogel; the drug-loaded hydrogel is formed by mixing blank hydrogel and composite nanoparticles.
[0007] Further preferably, the hydrophobic drug is an anti-inflammatory drug for treating brain injury.
[0008] Preferably, the raw materials for preparing liquid A in step (2) include tertiary amine compounds, natural polymers and epihalohydrin.
[0009] Further preferably, the tertiary amine compound includes at least one of dimethyldodecyl tertiary amine, dimethyloctyl tertiary amine, and dimethyltetradecyl tertiary amine, the natural polymer is a chitosan derivative, and the epihalohydrin is epichlorohydrin.
[0010] Further preferably, the tertiary amine compound is dimethyldodecyl tertiary amine, and the natural polymer is carboxymethyl chitosan.
[0011] Preferably, the preparation method of the liquid A is: first synthesize the antibacterial agent, and then mix the antibacterial agent with the natural polymer solution for reaction for 3-6 hours to obtain the liquid A.
[0012] Further preferably, the preparation method of the liquid A is: first synthesize the antibacterial agent, and then mix the antibacterial agent with the natural polymer solution for reaction for 3-5 hours to obtain the liquid A.
[0013] Further preferably, the preparation method of the liquid A is: first synthesize the antibacterial agent, and then mix the antibacterial agent with the natural polymer solution for 4 hours to obtain the liquid A.
[0014] Preferably, in the method for preparing liquid A, the amount of the antibacterial agent used is 10-20 mg.
[0015] Further preferably, in the method for preparing liquid A, the amount of the antibacterial agent used is 13-17 mg.
[0016] Further preferably, in the method for preparing liquid A, the amount of the antibacterial agent used is 15 mg.
[0017] Preferably, the raw materials for preparing liquid B in step (2) include a cross-linking agent and a hemostatic polypeptide.
[0018] Further preferably, the cross-linking agent is oxidized dextran.
[0019] Preferably, the preparation method of liquid B in step (2) is: mixing the cross-linking agent and the hemostatic polypeptide at 20-30° C. and reacting for 1-4 hours to obtain the liquid.
[0020] Further preferably, the preparation method of liquid B in step (2) is: mixing the cross-linking agent and the hemostatic polypeptide at 25° C. and reacting for 1-3 hours to obtain the liquid B.
[0021] Further preferably, the preparation method of liquid B in step (2) is: mixing the cross-linking agent and the hemostatic polypeptide at 25° C. and reacting for 2 hours to obtain the liquid B.
[0022] Preferably, the usage amount of the hemostatic polypeptide is 5-15 mg.
[0023] More preferably, the usage amount of the hemostatic polypeptide is 8-12 mg.
[0024] More preferably, the usage amount of the hemostatic polypeptide is 10 mg.
[0025] Preferably, in step (2), the volume ratio of liquid A to liquid B is 1:(2-4).
[0026] Further preferably, in step (2), the volume ratio of liquid A to liquid B is 1:(2.5-3.5).
[0027] Further preferably, in step (2), the volume ratio of liquid A to liquid B is 1:3.
[0028] Preferably, the mass percentage of liquid A is 1-3wt%, and the mass percentage of liquid B is 3-6wt%.
[0029] Further preferably, the mass percentage of liquid A is 1.5-2.5wt%, and the mass percentage of liquid B is 4-6wt%.
[0030] Further preferably, the mass percentage of liquid A is 2wt%, and the mass percentage of liquid B is 5wt%.
[0031] The second aspect of the present invention provides an application of the antibacterial hemostatic hydrogel loaded with composite nanoparticles in the preparation of wound repair materials.
[0032] The present application limits the amount of antibacterial agent added to 10-20 mg. At this time, the grafting rate of the antibacterial agent EPDMDAC in carboxymethyl chitosan is moderate, which will not lead to the subsequent addition of nanomaterials. On the one hand, its grafting rate is too high, resulting in the occupation of active sites that can be connected to the composite material, which not only affects the hemostatic performance of the hydrogel, but also on the other hand, when a blank hydrogel is subsequently synthesized, the number of reaction sites decreases sharply, causing the rheological and adhesion properties of the blank hydrogel to decrease. Similarly, on this basis, the amount of hemostatic polypeptide added is further limited to 8-12 mg.
[0033] The present application limits the ratio between the EPD-CMC solution and the RAD-0D solution in the blank hydrogel to 1:(2-4). A decrease in the ratio will lead to a decrease in the crosslinking density of the hydrogel, changing the gel-sol transition point, causing the loss modulus of the hydrogel to be much smaller than the storage modulus, causing viscous deformation, and the material to be liquid, which will weaken the adhesion performance of the gel. When the ratio of the two increases, the crosslinking density of the two increases, the loss modulus of the hydrogel is much larger than the storage modulus, the hydrogel becomes solid, and its adhesion and self-healing properties are relatively weakened.
[0034] Beneficial effects:
[0035] (1) The present invention utilizes the hydrophobic pores on the surface of mesoporous polydopamine nanospheres to load the anti-inflammatory hormone drug dexamethasone to obtain composite nanoparticles, which have the properties of anti-oxidation, anti-inflammatory, and inner layer repair.
[0036] (2) The present invention forms an antibacterial hemostatic gel by using the interaction force and "Schiff base reaction" of the composite nanoparticles and blank hydrogel. The antibacterial hemostatic gel has the ability to adsorb tissue exudate, has antibacterial properties, and can achieve controlled release of dexamethasone. It has antioxidant properties and can synergistically control the inflammatory microenvironment of the lesion site. It has high biocompatibility and tissue affinity and is suitable for filling and anti-inflammatory repair treatment of the postoperative site of brain injury.
[0037] (3) The antibacterial hemostatic gel prepared by the present invention has good stability, good mechanical properties, and good adhesion, self-healing and injectability. It also has good biocompatibility and self-degradation properties, can effectively stabilize drug components, and has high drug loading rate and encapsulation rate, which can achieve good drug release effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Particle size distribution diagram of mesoporous polydopamine nanospheres (mPDA) and composite nanomaterials (mPDA@DXMS).
[0039] Figure 2 Potential distribution diagram of mPDA and mPDA@DXMS.
[0040] Figure 3 (Left) is the TEM image of mPDA, and (right) is the TEM image of mPDA@DXMS.
[0041] Figure 4 Release curve obtained from in vitro drug release experiment of mPDA@DXMS.
[0042] Figure 5These are the UV-visible absorption spectra of dexamethasone (black line), mesoporous polydopamine nanospheres (red line), and mPDA@DXMS (blue line) in Example 1.
[0043] Figure 6 Infrared spectra of Liquid A synthesized using different amounts of antibacterial agents when synthesizing Liquid A.
[0044] Figure 7 Infrared spectra of liquid A (CMC-EPD), antibacterial agent (EPD) and carboxymethyl chitosan (CMC).
[0045] Figure 8 Infrared spectra of fluid B (OD-RAD), hemostatic polypeptide (PAD) and oxidized dextran (OD).
[0046] Fig. 9 This is the appearance of the blank hydrogel (left) and the antibacterial hemostatic hydrogel loaded with composite nanoparticles (right) in Example 1. It can be seen from the figure that the DXMS@mPDA@Gel composite hydrogel is a uniform and transparent gel without obvious particle deposition. It is preliminarily judged that the DXMS@mPDA composite nanoparticles are successfully and evenly adsorbed in the gel pores.
[0047] Fig.10 The left picture is the SEM image of the blank hydrogel, and the right picture is the antibacterial hemostatic hydrogel loaded with composite nanoparticles. Fig.11 In the figure, (1) is the rheological properties diagram of blank hydrogel and DXMS@mPDA@Gel, (2) is the shear rate-viscosity relationship curve in the rheological properties of blank hydrogel and DXMS@mmPDA@Gel, (3) is the step strain test in the rheological properties of blank hydrogel and DXMS@mPDA@Gel, and (4) is the self-healing performance diagram of the hydrogel in Example 1.
[0048] Fig.12 The degradation rate curves of blank hydrogel and antibacterial hemostatic hydrogel loaded with composite nanoparticles.
[0049] Fig.13 This is a graph showing the adhesion performance of the antibacterial hemostatic hydrogel loaded with composite nanoparticles in Example 1 on various organs of mice.
[0050] Fig.14 This is an antibacterial experiment of the blank hydrogel in Comparative Example 4 and Example 1 of the present invention, wherein (a) is a control experiment, (b) is added with the blank hydrogel in Comparative Example 4, and (c) is added with the blank hydrogel in Example 1.
[0051] Fig.15This is a hemostasis experiment of the blank hydrogel in Comparative Example 4 and Example 1 of the present invention, wherein (a) is a control experiment, (b) is added with the blank hydrogel in Comparative Example 4, and (c) is added with the blank hydrogel in Example 1. DETAILED DESCRIPTION
[0052] 1. The experimental materials used in the following examples are shown in the following table:
[0053]
[0054]
[0055] 2. The test instruments used in the experiment are shown in the following table:
[0056]
[0057] Example 1
[0058] A method for preparing an antibacterial hemostatic hydrogel loaded with composite nanoparticles comprises the following steps: (1) synthesizing composite nanoparticles; the composite nanoparticles are composed of mesoporous polydopamine nanospheres loaded with hydrophobic drugs; (2) synthesizing blank hydrogels; the blank hydrogels are formed by mixing liquid A and liquid B; (3) synthesizing drug-loaded hydrogels; the drug-loaded hydrogels are formed by mixing blank hydrogels and composite nanoparticles.
[0059] The hydrophobic drug is dexamethasone (DXMS).
[0060] The synthesis method of the composite nanoparticles in step (1) is as follows:
[0061] First, 1.0 g of nonionic surfactant poloxamer and 0.5 g of dopamine were dissolved in 100 mL of 50% ethanol solution, covered with plastic wrap, and holes were evenly pierced in the plastic wrap with a 200 uL pipette tip. The mixture was stirred at room temperature on a stirring table until dissolved to obtain a clear and transparent solution. After that, 2 mL of 3,3',5,5'-tetramethylbenzidine (TMB) was added dropwise at a speed of 500 rpm / min, and a white milky solution was obtained after stirring for 30 min. At the same speed, the temperature was adjusted to 25 °C, 5 mL of ammonia water was added dropwise, and a black solution was obtained after stirring for 2 h. The reaction was continued for 4 h to obtain a reaction solution. 2 mL of the reaction solution was aspirated into a 2 mL centrifuge tube (24 2 mL centrifuge tubes were prepared in advance), and the mixture was centrifuged in a refrigerated centrifuge (the centrifugal speed was 13500 rpm / min, and the time was 15 min). The supernatant was discarded and 2 mL Wash with 50% ethanol and shake well, continue centrifugation, repeat the above operation twice, finally add 500 μL pure water to dissolve the precipitate after centrifugation, and resuspend by ultrasound to obtain mesoporous polydopamine nanosphere solution (mPDA);
[0062] A 1 mL, 1 mg / mL dexamethasone (DXMS) solution was added to 1 mL of a 1 mg / mL mesoporous polydopamine nanosphere solution, and after stirring at 400 rpm / min for 24 h, the mixture was centrifuged and washed to obtain a composite nanomaterial (mPDA@DXMS).
[0063] The raw materials for preparing liquid A in step (2) include tertiary amine compounds, natural polymers and epihalohydrin, wherein the tertiary amine compound is dimethyldodecyl tertiary amine (EPD), the natural polymer is carboxymethyl chitosan, and the epihalohydrin is epichlorohydrin.
[0064] The preparation method of the A liquid is as follows: firstly synthesize the antibacterial agent, then mix 15 mg of the antibacterial agent with 5 mL.3% carboxymethyl chitosan solution (CMC) for 4 hours, and then dialyze with a 1000 KDa dialysis bag for 24 hours to obtain the A liquid.
[0065] The synthesis method of the antibacterial agent (EPDMDAC) is as follows: 0.01 mol of dimethyldodecyl tertiary amine and 0.04 mmol of epichlorohydrin are reacted at a temperature of 80° C. for 1 hour. When the mixed reactant solution changes from transparent to dark yellow, the reaction product is precipitated with ether, and the crude EPDMDAC is obtained by centrifugation. The crude EPDMDAC is then ultrasonically washed with ether for 3 times and dried in a vacuum to obtain the antibacterial agent (EPDMDAC).
[0066] The raw materials for preparing liquid B in step (2) include a cross-linking agent and a hemostatic polypeptide.
[0067] The cross-linking agent is oxidized dextran (0D), and the preparation method of the oxidized dextran is as follows: 5g of dextran is dissolved in 250mL of distilled water to obtain a dextran solution, 5g of sodium periodate is dissolved in 5mL of distilled water to obtain a sodium periodate solution, the sodium periodate solution is added dropwise to the dextran solution, and then stirred for 3.5h at room temperature in the dark to obtain a mixture, finally, 3mL of ethylene glycol is added to the mixture to react unreacted sodium periodate, and finally stirred for another 1h, and the resulting product is dialyzed against distilled water (MWCO 3500Da) for 3 days and freeze-dried to obtain oxidized dextran.
[0068] The preparation method of liquid B in step (2) is: adding 10 mg of hemostatic polypeptide to 5 ml of 5wt% oxidized dextran solution at 25°C and reacting for 2 hours; the nucleotide sequence of the hemostatic polypeptide is arginine (R)-alanine (A)-aspartic acid (D)-alanine (A)-arginine (R)-glycine (G)-aspartic acid (D)-lysine (K).
[0069] (2) Synthesis of blank hydrogel: 2 wt% of liquid A and 5 wt% of liquid B (using distilled water as solvent) were mixed in a volume ratio of 1:3 to obtain a blank hydrogel.
[0070] (3) Synthesis of drug-loaded hydrogel: The composite nanoparticle solution was dispersed in liquid A at a volume ratio of 1:1 to obtain a first solution, and then the first solution and liquid B were mixed at a volume ratio of 1:3 to obtain an antibacterial hemostatic hydrogel loaded with composite nanoparticles (DXMS@mPDA@Gel).
[0071] Example 2
[0072] The preparation method of liquid B in step (2) is: adding 8 mg of hemostatic polypeptide to 5 mL of 5 wt% oxidized dextran solution at 25° C. and reacting for 2 hours; the nucleotide sequence of the hemostatic polypeptide is arginine (R)-alanine (A)-aspartic acid (D)-alanine (A)-arginine (R)-glycine (G)-aspartic acid (D)-lysine (K).
[0073] (2) Synthesis of blank hydrogel: 2 wt% of liquid A and 5 wt% of liquid B (using distilled water as solvent) were mixed in a volume ratio of 1:2 to obtain a blank hydrogel.
[0074] The rest is the same as in Example 1.
[0075] Example 3
[0076] The preparation method of the A liquid is as follows: firstly synthesize the antibacterial agent, then mix 10 mg of the antibacterial agent with 5 mL of 3% carboxymethyl chitosan solution (CMC) for 4 hours, and then dialyze with a 1000 KDa dialysis bag for 24 hours to obtain the A liquid.
[0077] The synthesis method of the antibacterial agent (EPDMDAC) is as follows: 0.01mmol of dimethyldodecyl tertiary amine and 0.04mmol of epichlorohydrin are reacted at a temperature of 80°C for 1 hour. When the mixed reactant solution changes from transparent to dark yellow, the reaction product is precipitated with ether, and the crude EPDMDAC is obtained by centrifugation. The crude EPDMDAC is then ultrasonically washed with ether for 3 times and dried in a vacuum to obtain the antibacterial agent (EPDMDAC).
[0078] The raw materials for preparing liquid B in step (2) include a cross-linking agent and a hemostatic polypeptide.
[0079] The cross-linking agent is oxidized dextran (OD), and the preparation method of the oxidized dextran is as follows: 5 g of dextran is dissolved in 250 mL of distilled water to obtain a dextran solution, sodium periodate is dissolved in 5 mL of distilled water to obtain a sodium periodate solution, the sodium periodate solution is added dropwise to the dextran solution, and then stirred for 3.5 hours at room temperature in the dark to obtain a mixture, and finally, 3 mL of ethylene glycol is added to the mixture to react unreacted sodium periodate, and finally stirred for another 1 hour, and the resulting product is dialyzed against distilled water (MWCO 1400Da) for 3 days and freeze-dried to obtain oxidized dextran.
[0080] The preparation method of liquid B in step (2) is: adding 10 mg of hemostatic polypeptide to 5 ml of 5wt% oxidized dextran solution at 25°C and reacting for 2 hours; the nucleotide sequence of the hemostatic polypeptide is arginine (R)-alanine (A)-aspartic acid (D)-alanine (A)-arginine (R)-glycine (G)-aspartic acid (D)-lysine (K).
[0081] (2) Synthesis of blank hydrogel: 2 wt% of liquid A and 5 wt% of liquid B (using distilled water as solvent) were mixed in a volume ratio of 1:4 to obtain a blank hydrogel.
[0082] The rest is the same as in Example 1.
[0083] Comparative Example 1
[0084] The preparation method of the A liquid is as follows: firstly synthesize the antibacterial agent, then mix 25 mg of the antibacterial agent with 5 mL of 3% carboxymethyl chitosan solution (CMC) for reaction for 3 hours, and then dialyze with a 1000 KDa dialysis bag for 24 hours to obtain the A liquid.
[0085] The rest is the same as in Example 1.
[0086] Comparative Example 2
[0087] The preparation method of liquid B in step (2) is: adding 20 mg of hemostatic polypeptide to 5 ml of 5wt% oxidized dextran solution at 25°C and reacting for 1.5 hours; the nucleotide sequence of the hemostatic polypeptide is arginine (R)-alanine (A)-aspartic acid (D)-alanine (A)-arginine (R)-glycine (G)-aspartic acid (D)-lysine (K).
[0088] The rest is the same as in Example 1.
[0089] Comparative Example 3
[0090] (2) Synthesis of blank hydrogel: 2 wt% of liquid A and 5 wt% of liquid B (using distilled water as solvent) were mixed in a volume ratio of 1:5 to obtain a blank hydrogel.
[0091] The rest is the same as in Example 1.
[0092] Comparative Example 4
[0093] A method for preparing an antibacterial hemostatic hydrogel loaded with composite nanoparticles comprises the following steps: (1) synthesizing composite nanoparticles; the composite nanoparticles are composed of mesoporous polydopamine nanospheres loaded with hydrophobic drugs; (2) synthesizing blank hydrogels; the blank hydrogels are formed by mixing liquid A and liquid B; (3) synthesizing drug-loaded hydrogels; the drug-loaded hydrogels are formed by mixing blank hydrogels and composite nanoparticles.
[0094] The hydrophobic drug is dexamethasone (DXMS).
[0095] The synthesis method of the composite nanoparticles in step (1) is as follows:
[0096] First, 1.0 g of nonionic surfactant poloxamer and 0.5 g of dopamine were dissolved in 100 mL of 50% ethanol solution, covered with plastic wrap, and holes were evenly pierced in the plastic wrap with a 200 uL pipette tip. The mixture was stirred at room temperature on a stirring table until dissolved to obtain a clear and transparent solution. After that, 2 mL of 3,3',5,5'-tetramethylbenzidine (TMB) was added dropwise at a speed of 500 rpm / min, and a white milky solution was obtained after stirring for 30 min. At the same speed, the temperature was adjusted to 25 °C, 5 mL of ammonia water was added dropwise, and a black solution was obtained after stirring for 2 h. The reaction was continued for 4 h to obtain a reaction solution. 2 mL of the reaction solution was aspirated into a 2 mL centrifuge tube (24 2 mL centrifuge tubes were prepared in advance), and the mixture was centrifuged in a refrigerated centrifuge (the centrifugal speed was 13500 rpm / min, and the time was 15 min). The supernatant was discarded and 2 mL Wash with 50% ethanol and shake well, continue centrifugation, repeat the above operation twice, finally add 500 μL pure water to dissolve the precipitate after centrifugation, and resuspend by ultrasound to obtain mesoporous polydopamine nanosphere solution (mPDA);
[0097] A 1 mL, 1 mg / mL dexamethasone (DXMS) solution was added to 1 mL of a 1 mg / mL mesoporous polydopamine nanosphere solution, and after stirring at 400 rpm / min for 24 h, the mixture was centrifuged and washed to obtain a composite nanomaterial (mPDA@DXMS).
[0098] In the step (2), the raw material for preparing liquid A is a natural polymer, and the natural polymer is carboxymethyl chitosan. Carboxymethyl chitosan is dissolved in water to prepare liquid A with a mass percentage of 2wt%.
[0099] The raw material for preparing liquid B in step (2) is a cross-linking agent.
[0100] The cross-linking agent is oxidized dextran (OD), and the preparation method of the oxidized dextran is as follows: 5 g of dextran is dissolved in 250 mL of distilled water to obtain a dextran solution, 5 g of sodium periodate is dissolved in 5 mL of distilled water to obtain a sodium periodate solution, the sodium periodate solution is added dropwise to the dextran solution, and then stirred for 3.5 hours at room temperature in the dark to obtain a mixture, and finally, 3 mL of ethylene glycol is added to the mixture to react unreacted sodium periodate, and finally stirred for another 1 hour, and the resulting product is dialyzed against distilled water (MWC0 3500Da) for 3 days and freeze-dried to obtain oxidized dextran.
[0101] The oxidized dextran was dissolved in water to prepare a liquid B with a mass percentage of 5 wt%.
[0102] (2) Synthesis of blank hydrogel: 2 wt% of liquid A and 5 wt% of liquid B (using distilled water as solvent) were mixed in a volume ratio of 1:3 to obtain a blank hydrogel.
[0103] (3) Synthesis of drug-loaded hydrogel: The composite nanoparticle solution was dispersed in liquid A at a volume ratio of 1:1 to obtain a first solution, and then the first solution and liquid B were mixed at a volume ratio of 1:3 to obtain an antibacterial hemostatic hydrogel loaded with composite nanoparticles (DXMS@mPDA@Gel).
[0104] Performance Evaluation
[0105] (1) Determination of encapsulation efficiency and loading rate of composite nanoparticles (DXMS@mPDA):
[0106] 1. Preparation of standard curve: Weigh 5 mg of demethasone standard substance into a beaker, add appropriate amount of ultrapure water to dissolve, then transfer to a 5 mL volumetric flask, make up to 1 mg / mL demethasone solution, dilute to 25, 12.5, 6.25, 3.125, 1.5625 ug / mL standard solution, measure the absorbance at 242 nm with UV-2600i ultraviolet spectrophotometer, and draw a standard curve with demethasone concentration as the horizontal axis and absorbance as the vertical axis.
[0107] 2. After ultrafiltration of the DXMS@mPDA synthesized in the embodiment and the comparative example using a 100 kd ultrafiltration tube, the filtrates below and above the ultrafiltration tube were collected, and the volume difference between the two was calculated. Then, the following solution was appropriately diluted, and the absorbance of the solution was tested using UV-2600i. The standard curve was substituted to calculate the drug mass in the following solution. The drug mass in the solution was subtracted from the total added mass to obtain the loaded drug mass. The encapsulation efficiency and loading rate were calculated according to the following formula:
[0108] Encapsulation efficiency = loaded dexamethasone mass / theoretical total added dexamethasone Loading rate = loaded dexamethasone mass / sum of the mass of mesoporous polydopamine nanospheres and loaded dexamethasone
[0109] The test results are shown in Table 1.
[0110] (2) Material characterization.
[0111] 1. Particle size and potential test
[0112] The nanoparticles were appropriately diluted with ultrapure water (diluted 10 times), and then the particle size and potential of the samples were tested using the particle size and potential mode in the Zetasizer Nano ZS90 particle size analyzer. As shown in the figure, the average particle size of mPDA is 85nm, the potential is -38.3mV, and the average particle size of mPDA@DXMS is 80nm, and the potential is -41.5mV.
[0113] 2. Transmission electron microscopy (TEM) test:
[0114] After diluting the sample 10 times with ultrapure water, take 70uL and drop it on a special copper mesh. After 3 minutes, remove the excess liquid with filter paper, then add 70uL of 2% uranyl acetate for negative staining. After 3 minutes, remove the excess liquid with filter paper, dry it naturally, and observe the morphology of the synthesized nanoparticles with a TEM electron microscope, as shown in the figure.
[0115] 3. Sample stability test
[0116] In order to evaluate the stability of the composite nanoparticles, the composite nanoparticles and PBS solution were mixed in a ratio of 1:1 and then allowed to stand at room temperature. The particle size was tested for 2, 4, 6, 8, 10, 12, and 24 h to evaluate the particle size stability of the samples. As the standing time increased, the average particle size of the composite nanoparticles changed less, demonstrating that mPDA@DXMS had good stability.
[0117] 4. Sample Release Analysis
[0118] In order to evaluate the drug release behavior of the composite nanoparticle system, an in vitro drug release experiment was implemented. Specifically, 2 mL of composite nanoparticles were sealed in a dialysis bag, placed in a sample bottle containing 10 mL of pH 7.4 buffer, and continuously shaken at 37°C and 150 r / min. Every 2 hours (when the time exceeds 10 hours, the time point becomes every 5 hours), 2 mL of the solution was centrifuged, and then 2 mL of the corresponding PBS was supplemented in the centrifugal product. The absorbance at 250 nm in the supernatant was measured by ultraviolet spectroscopy. The release amount at different times was calculated according to the standard curve. As shown in the figure, within the time range of 2-24 hours, the drug release rate of the composite nanoparticles increased from 15.13% to 72.95%.
[0119] 5. UV-visible absorption spectrum test: UV-2600i UV spectrophotometer was used to measure the UV-visible absorption spectra of DXMS solution, mPDA, and mPDA@DXMS.
[0120] (2) Related tests and results of hydrogel materials.
[0121] 1. Scanning Electron Microscope (SEM):
[0122] 1.1 Sample preparation: Stick the conductive glue on the sample table, then stick a clean thin copper sheet on the conductive glue, drop the sample on the copper sheet in small amounts and multiple times, and wait for the solvent to evaporate and dry completely.
[0123] Preparation of hydrogel samples: Cut the freshly prepared hydrogel samples into 1*1*1cm 3 The square gel block was added with distilled water and placed in a 4°C refrigerator for 24 hours. It was then quickly frozen in liquid nitrogen for 30 minutes and immediately placed in a freeze dryer for 24 hours. The block gel sample was directly glued to the conductive glue.
[0124] 1.2 Gold spraying test:
[0125] The Oxford Quorum SC7620 sputtering coater was used to spray gold for 45s at 10mA; the sample morphology was then photographed using a TESCANMIRA LMS scanning electron microscope, and the accelerating voltage was 3kV when the morphology was photographed. The morphology of the blank hydrogel (Gel) and the drug-loaded hydrogel (DXMS@mPDA@Gel) was observed. As shown in the figure, both the Gel and DXMS@mPDA@Gel composite hydrogels showed a typical three-dimensional network structure of the gel. And compared with the blank gel, uniformly dispersed composite nanoparticles with a particle size of about 120nm were observed in the pores of the DXMS@mPDA@Gel composite hydrogel. This is consistent with the particle size of the DXMS@mPDA composite nanoparticles. This shows that the DXMS@mPDA@Gel composite hydrogel was successfully synthesized.
[0126] 2. Fourier transform infrared spectroscopy
[0127] Take 20 mg of dry gel sample and place it between two glass slides to form a sheet. In a dry environment, place the ATR accessory in the optical path of the spectrometer, scan the air background, and then place the block / film sample surface close to the crystal surface of the ATR accessory, and then collect the infrared spectrum of the sample with a resolution of 4 cm -1 , the scanning times are 32 times, and the test wave number range is 500-4000cm -1 , as shown in the figure, at 1471cm -1 The characteristic peak of the antibacterial agent appears at 3300cm -1 The obvious change of the peak at may be caused by the grafting of the hemostatic peptide RADARGDK onto the oxidized dextran.
[0128] 3. Rheological properties and self-healing performance tests.
[0129] Prepare hydrogel samples with a diameter of 20 mm and a height of 2 mm. Use a Mars 60 rheometer to characterize the rheological properties of the hydrogel. Set γ = 0.1-1000% and f = 1 Hz to perform an oscillation rate sweep test at 25 ± 0.2 ° C. Keep the temperature and strain (γ = 1%) fixed, and only change the frequency (0.1-100 Hz) to obtain the shear rate-viscosity relationship curve. Use a rheometer to measure the rheological properties of the hydrogel.
[0130] At the same time, the gel was labeled with FITC (yellow-green fluorescence) and rhodamine B (red fluorescence) respectively. After the gel was formed, it was cut with a scalpel and the two gel blocks of different colors were spliced together. After a period of time, the changes in the hydrogel were observed.
[0131] The results are shown in the figure. When the strain range in (1) is 0.1 - 100%, the G' of the gel is distributed between 30 - 40 Pa, and the material mainly undergoes elastic deformation, and the gel structure is well maintained. While the G'' is distributed between 0 - 10 Pa, G' is greater than G''. When the strain range is greater than 100%, an intersection appears between G' and G'', and at this time, the sample is at the gel - sol transition point, that is, the state of the sample begins to change. When G' < G'', the material mainly undergoes viscous deformation, indicating that the sample mainly exhibits liquid characteristics, indicating that the gel structure collapses at this time; The viscosity of the hydrogel prepared in (2) decreases with the increase of stress, that is, the shear - thinning effect appears. The above results all indicate that this hydrogel has injectability, and its visualization results are shown in the inset. The gel labeled with FITC fluorescence can be injected into a uniform strip by a syringe, thus meeting the treatment of wounds with different shapes. Gel self - healing refers to the ability to approach or reach the state before damage in terms of morphology, performance, etc. after self - repair when the material is externally damaged. As shown in Figure (4), gels are labeled with FITC (yellow - green fluorescein) and rhodamine B (red fluorescein) respectively. After gel formation, they are cut with a scalpel, and two gel blocks of different colors are spliced together. After placing for 5 minutes, the color at the interface shows obvious fusion, indicating that molecules move at the interface at this time, and the spliced gap heals significantly. The above can show that this gel has good self - healing performance, and this characteristic is beneficial for the gel to self - adhere after injection, maintain a good extended state of coverage, and maintain the contact surface at the lesion site.
[0132] 4. Gel degradation analysis
[0133] 4.1 Enzymatic hydrolysis
[0134] Take a certain mass (W0) of the hydrogel and put it into PBS solution, add the corresponding degradation enzyme, regularly take out the hydrogel, rinse it with deionized water after taking it out, freeze - dry it, and measure the mass of the freeze - dried hydrogel (W t ), and calculate the degradation rate of the hydrogel.
[0135] Degradation rate (%) = (W0 - W t ) / W0 × 100%
[0136] The specific operation is as follows: Add 2.5 g of trypsin and 25 mg of lysozyme solid to 50 mL of PBS solution with pH = 7.4. Wait for the solid to dissolve to form a uniform solution. Weigh 50 mg (W0) of the freeze - dried hydrogel and put it into a 10 - mL sample bottle. Take 5 mL of the composite enzyme solution and add it to the sample bottle, and then put it into an oscillating incubator (37 °C, 70 rpm)
[0137] Samples were taken out regularly (1, 3, 5, 7, 14, 21 d), rinsed with deionized water and placed in a -20 °C refrigerator overnight. The samples were taken out the next day and freeze-dried for 12 h. The mass of the freeze-dried hydrogel (Wt) was measured, and the degradation rate of the hydrogel was calculated according to the formula.
[0138] As shown in the figure, hydrogel materials have good biocompatibility and degradability. Under the physiological environment of the body, they can be degraded from high-molecular and macromolecular substances into small-molecule substances that are harmless to the body through hydrolysis and enzymolysis. These small-molecule degradation products usually exist in the body itself and are completely absorbed and excreted through the body's metabolism, without toxic side effects to the body. The degradation performance of the hydrogel was verified by enzymolysis experiments.
[0139] The mass loss curves of Gel and DXMS@mPDA@Gel hydrogels after degradation in the composite enzyme solution at pH = 7.4 are shown in the figure. The gel mass loss of Gel and DXMS@mPDA@Gel hydrogels gradually increased with time, and the degradation rates of Gel and DXMS@mPDA@Gel hydrogels were 75% and 70% at 7d, respectively, and the change trend slowed down after 7d. This is attributed to the cleavage of Schiff base bonds, cation-π and electrostatic interactions in the composite enzyme solution. In addition, it can be seen that after the addition of DXMS@mPDA nanoparticles, the mass loss rate of the gel under the same conditions was significantly reduced. This may be because the introduction of mPDA promotes additional cross-linking points within the hydrogel matrix, resulting in a more stable internal structure of the hydrogel, thereby reducing the gel loss rate.
[0140] 5. Adhesion properties of gel
[0141] First, add 10 mL of antibacterial hemostatic hydrogel loaded with composite nanoparticles into a circular culture dish with a diameter of 35 mm, and then place fresh mouse spleen, kidney, heart, lung, and liver in the circular container for culture. After 3 minutes, turn the culture dish upside down.
[0142] As shown in the figure, the hydrogel is in a transparent colloid state. After the culture dish with fresh organs adhered to it is inverted, the tissues are firmly adhered to the gel, and the organs do not fall off when inverted, indicating that the gel can adhere to various fresh organs. It can be seen from the above results that the gel prepared by the present invention has good adhesion performance to mouse heart, liver, spleen, lung and kidney tissues.
[0143] 6. Antibacterial properties of gel
[0144] The antibacterial activity of the hydrogel can also be tested by plate diffusion experiment. All hydrogels with d = 10 mm were sterilized under ultraviolet light for 0.5 h, and then different samples were placed on agar plates coated with quantitative bacterial solution and cultured in an incubator at 37°C for 24 h. The antibacterial performance of the hydrogel was evaluated based on the diameter of the inhibition zone. The results are shown in Fig.14 As shown, (a) is a control experiment, in which no blank hydrogel is added, (b) is the blank hydrogel in Comparative Example 4, in which the blank hydrogel is not grafted with an antibacterial agent, and it can be found that the inhibition zone is smaller, and (c) is the blank hydrogel grafted with an antibacterial agent in Example 1, in which it can be clearly found that the inhibition zone is larger.
[0145] 7. Gel hemostatic properties
[0146] Liver injury hemostasis experiment: First, the experimental animals were fasted for 24 hours, and then weighed and anesthetized intramuscularly according to the corresponding dose on the second day. Then the limbs and head were fixed on the operating table, tracheal intubation was performed and connected to the respiratory anesthesia machine, and then the abdominal skin was prepared and disinfected, and the liver was exposed under sterile conditions. After being freed, a scalpel was used to cut a wound about 0.5 cm long and 0.05 cm deep on the surface of the liver. After observing the blood flow, an area of 5*5cm 2 Place gauze pad on the liver and apply hydrogel dressing to the wound surface. Press slightly and wait for the same amount of time to see if the wound stops bleeding. Fig.15 As shown, (a) is a control test without adding hydrogel, (b) is a blank hydrogel in Comparative Example 4, which is not grafted with hemostatic polypeptide, and it can be clearly found that the wound has not stopped bleeding, (c) is a blank hydrogel grafted with hemostatic polypeptide in Example 1, and it can be clearly found that the wound has stopped bleeding.
[0147] The above-mentioned self-healing performance and adhesion performance tests were performed on the nanoparticle-loaded antibacterial hemostatic hydrogels prepared in Example and Comparative Examples 1-3. The test results are shown in Table 1.
[0148] The evaluation of the healing performance test is the placement time. The longer the placement time, the worse the self-healing performance.
[0149] Table 1
[0150] Example Placement time (mmin) Example 1 5 Example 2 5 Example 3 5 Comparative Example 1 15 Comparative Example 2 16 Comparative Example 3 6
[0151] Compared with Example 1, the excessive amount of antibacterial agent used in Comparative Example 1 will lead to an excessively high grafting rate, resulting in the occupation of the connectable active sites in the composite nanoparticles, which will reduce the self-healing performance of the hydrogel. The excessive amount of hemostatic polypeptide used in Comparative Example 2 is similar to the principle of Comparative Example 1, which will also reduce the self-healing performance of the hydrogel. The ratio of liquid A and liquid B in Comparative Example 3 is reduced, which will lead to a decrease in the cross-linking density of the blank hydrogel, resulting in a decrease in the self-healing performance.
Claims
1. An antibacterial hemostatic hydrogel loaded with composite nanoparticles, characterized in that Prepared by the following steps: (1) Synthesis of composite nanoparticles: The composite nanoparticles are composed of mesoporous polydopamine nanospheres loaded with hydrophobic drugs; (2) Synthesis of blank hydrogel: The blank hydrogel is prepared by mixing liquid A and liquid B; wherein the preparation method of liquid A is as follows: first synthesize an antibacterial agent, then mix 10-20 mg of the antibacterial agent with 5 mL of 3% carboxymethyl chitosan solution for 4 hours, and then dialyze with a 1000KDa dialysis bag for 24 hours to obtain the antibacterial agent; the synthesis method of the antibacterial agent is as follows: 0.01 mmol of dimethyldodecyl tertiary amine and 0.04 mmol of epichlorohydrin are reacted at a temperature of 80°C for 1 hour, when the mixed reaction solution changes from transparent to dark yellow, the reaction product is precipitated with ether, centrifuged to obtain a crude antibacterial agent, and then the crude antibacterial agent is ultrasonically washed with ether for 3 times and dried in a vacuum to obtain the antibacterial agent; (3) Synthesis of drug-loaded hydrogel: The composite nanoparticle solution is dispersed in liquid A at a volume ratio of 1:1 to obtain a first solution, and then the first solution and liquid B are mixed at a volume ratio of 1:3 to obtain an antibacterial hemostatic hydrogel loaded with composite nanoparticles; Wherein, in step (2), the raw materials for preparing liquid B include a cross-linking agent and a hemostatic polypeptide, the volume ratio of liquid A to liquid B is 1:(2-4), the mass percentage of liquid A is 1-3wt%, and the mass percentage of liquid B is 3-6wt%.
2. The antibacterial hemostatic hydrogel loaded with composite nanoparticles according to claim 1, characterized in that: The preparation method of liquid B in step (2) is: mixing the cross-linking agent and the hemostatic polypeptide at 20-30° C. and reacting for 1-4 hours to obtain the liquid B.
3. The antibacterial hemostatic hydrogel loaded with composite nanoparticles according to claim 2, characterized in that: The usage amount of the hemostatic polypeptide is 5-15 mg, and the hydrophobic drug includes dexamethasone.
4. An antibacterial hemostatic hydrogel loaded with composite nanoparticles, characterized in that The invention comprises a mixed blank hydrogel and composite nanoparticles, wherein the composite nanoparticles are formed by loading a hydrophobic drug on mesoporous polydopamine nanospheres, and the blank hydrogel is formed by mixing liquid A and liquid B; wherein the antibacterial agent is first synthesized, and then 10-20 mg of the antibacterial agent is mixed with 5 mL of a 3% natural polymer solution for reaction for 3-6 hours to obtain the liquid A; The cross-linking agent and the hemostatic polypeptide are mixed and reacted for 1-4 hours to obtain the liquid B, the volume ratio of the liquid A to the liquid B is 1:(2-4), the mass percentage of the liquid A is 1-3wt%, and the mass percentage of the liquid B is 3-6wt%.
5. The antibacterial hemostatic hydrogel loaded with composite nanoparticles according to claim 4, characterized in that: The usage amount of the hemostatic polypeptide is 5-15 mg.
6. The antibacterial hemostatic hydrogel loaded with composite nanoparticles according to claim 6, characterized in that The hydrophobic drug includes dexamethasone.
Citation Information
Patent Citations
An antibacterial, adhesive, and self-healing hydrogel, its preparation method, and its applications.
CN114668897B
Hyperbranched polylysine-containing hydrogel carrier material and preparation method thereof
CN114984244A